2022
DOI: 10.3390/cancers14061536
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Focused Ultrasound in the Treatment of Genitourinary Cancers

Abstract: Traditional cancer treatments have been associated with substantial morbidity for patients. Focused ultrasound offers a novel modality for the treatment of various forms of cancer which may offer effective oncological control and low morbidity. We performed a review of PubMed articles assessing the current applications of focused ultrasound in the treatment of genitourinary cancers, including prostate, kidney, bladder, penile, and testicular cancer. Current research indicates that high-intensity focused ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…Sonodynamic therapy was introduced in 1989 with the aim of improving the effectiveness of drug therapy and also reducing drug-related systemic toxicity. According to previous studies, ultrasound irradiation can enhance the antitumor effect of chemotherapeutic drugs in vitro ( Panzone et al, 2022 ), and the mechanism of increased chemosensitivity of ultrasound-treated cells is not well understood, while cavitation and resealing of cell membranes by acoustic pressure are thought to be the main reasons for increasing the intracytoplasmic concentration of the administered drugs ( Carstensen et al, 2000 ; Maxwell et al, 2013 ). In this study, CCK8 assays showed that LFU inhibited sarcoma cell growth and proliferation in a dose- and time-dependent manner, and that the combination of LFU with PTX significantly increased the inhibition rate of sarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Sonodynamic therapy was introduced in 1989 with the aim of improving the effectiveness of drug therapy and also reducing drug-related systemic toxicity. According to previous studies, ultrasound irradiation can enhance the antitumor effect of chemotherapeutic drugs in vitro ( Panzone et al, 2022 ), and the mechanism of increased chemosensitivity of ultrasound-treated cells is not well understood, while cavitation and resealing of cell membranes by acoustic pressure are thought to be the main reasons for increasing the intracytoplasmic concentration of the administered drugs ( Carstensen et al, 2000 ; Maxwell et al, 2013 ). In this study, CCK8 assays showed that LFU inhibited sarcoma cell growth and proliferation in a dose- and time-dependent manner, and that the combination of LFU with PTX significantly increased the inhibition rate of sarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, research to improve cancer cell treatment performance through the development of microrobots with controllable drug-release abilities is being actively conducted. Several methods facilitate active drug release based on external stimuli such as near-infrared (NIR), ultraviolet (UV), alternating magnetic field (AMF), and focused ultrasound (FUS) stimuli, which allow microrobots to release a large amount of drug at the desired time to improve cancer cell treatment performance. NIR is applied in the form of a laser and can deliver high energy to the target area. Although UV is more difficult to transmit with high energy compared to NIR, it has the advantage of being able to transmit energy to relatively deep tissues. AMF has a disadvantage in that the size of the coil increases as the application target becomes larger, but it has the advantage of being able to stimulate deep into the tissue. FUS is widely used in the treatment of cells, biological molecules, and tissues through mechanical force while being able to deliver energy locally and has the advantage of penetrating deeper into tissues compared to other energy sources. …”
Section: Introductionmentioning
confidence: 99%
“…Focused ultrasound (FUS) can penetrate deep and directly induce localized hyperthermia without intermediate co-factors in biological tissues 25,26 . In fact, it has been used for tissue ablation in patients at relatively high temperatures (>60 °C) [27][28][29][30] , and for controlling heat-sensitive transgene expression in vivo at mildly elevated temperatures (42 -43 °C) [31][32][33][34][35][36] . We have previously developed FUS-inducible CAR (FUS-CAR)-T cells that can be acoustogenetically activated by FUS for cancer therapy with reduced off-tumour toxicities 37 .…”
mentioning
confidence: 99%